2016
DOI: 10.1186/s12879-016-1623-y
|View full text |Cite
|
Sign up to set email alerts
|

Changing distribution of age, clinical severity, and genotypes of rotavirus gastroenteritis in hospitalized children after the introduction of vaccination: a single center study in Seoul between 2011 and 2014

Abstract: BackgroundThis study aimed to explore changes in clinical epidemiology and genotype distribution and their association among hospitalized children with rotavirus gastroenteritis after the introduction of vaccines.MethodsBetween November 2010 and October 2014, hospitalized children with acute gastroenteritis were enrolled. Rotavirus genotypes were confirmed through reverse transcription-polymerase chain reaction (RT-PCR), semi-nested PCR, and sequencing. Clinical information including vaccination status and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 52 publications
8
20
0
Order By: Relevance
“…Interestingly, we found a significant association between G8P[8] genotype and dehydration signs, febrile temperature or vomiting episodes. Shim et al (2016) found that G2P [4] was significantly associated with greater vomiting-related severity compared to other genotypes, including G1P [8]. However, the association between G2P[4] and clinical severity itself is mostly consistent with the results of several studies from the pre-vaccine era (Bern et al, 1992;Cascio et al, 2001).…”
Section: Discussionsupporting
confidence: 63%
“…Interestingly, we found a significant association between G8P[8] genotype and dehydration signs, febrile temperature or vomiting episodes. Shim et al (2016) found that G2P [4] was significantly associated with greater vomiting-related severity compared to other genotypes, including G1P [8]. However, the association between G2P[4] and clinical severity itself is mostly consistent with the results of several studies from the pre-vaccine era (Bern et al, 1992;Cascio et al, 2001).…”
Section: Discussionsupporting
confidence: 63%
“…The study results documented that most of the hospitalizations (72%) occurred among children < 3 years of age, which coincided with the international data [13][14][15][16]. The fact that no statistically significant differences in age between patients admitted to Intensive Care Unit and patients admitted to general divisions were detected may suggest that there were other factors influencing the severity of the disease.…”
Section: Discussionsupporting
confidence: 83%
“…Additionally, we found that rotavirus infection (in mostly unvaccinated children in this study) was the primary pathogenic cause of severe clinical gastroenteritis. Because this study was performed between 2012 and 2013, which corresponds to 5–6 years after the introduction of the rotavirus vaccine in Korea (the rate of rotavirus vaccination more than 2 times was reported to be 65.6% in Seoul, and nationwide rate 52.4% in 2013 by Korean National Immunization Survey; http://www.cdc.go.kr ), the age of children vulnerable to rotavirus infection seems to have transiently increased over the study period ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Viral double stranded RNA and DNA were extracted from the supernatant using the QIAamp MiniElute Virus Spin Kit (Qiagen, Hilden, Germany). PCR was performed to detect adenovirus ( 15 ) and reverse transcription PCR (RT-PCR) was performed to detect rotavirus ( 8 ), norovirus ( 16 ), and astrovirus ( 17 ) as described previously ( 18 ). Multiplex PCR using a Seeplex Diarrhea-V ACE detection kit (Seegene Inc., Seoul, Korea) was also performed to detect astrovirus, group A rotavirus, enteric adenovirus, and norovirus, according to the manufacturer's instructions ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation